2017
DOI: 10.1038/s41598-017-09348-1
|View full text |Cite
|
Sign up to set email alerts
|

An expandable embryonic stem cell-derived Purkinje neuron progenitor population that exhibits in vivo maturation in the adult mouse cerebellum

Abstract: The directed differentiation of patient-derived induced pluripotent stem cells into cell-type specific neurons has inspired the development of therapeutic discovery for neurodegenerative diseases. Many forms of ataxia result from degeneration of cerebellar Purkinje cells, but thus far it has not been possible to efficiently generate Purkinje neuron (PN) progenitors from human or mouse pluripotent stem cells, let alone to develop a methodology for in vivo transplantation in the adult cerebellum. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…We hypothesized that loss of Adnp may cause developmental and functional defects of embryonic cerebellum. To test this hypothesis, we took use of ESC-based in vitro cerebellar neuron differentiation as a model system, and adapted the published SFEB protocols that have been shown to efficiently induce ESCs into GABA receptor alpha 6 + granule cells and L7 + Purkinje neurons via Math1 and Ncam expressing precursors 2427 (Fig. 8a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that loss of Adnp may cause developmental and functional defects of embryonic cerebellum. To test this hypothesis, we took use of ESC-based in vitro cerebellar neuron differentiation as a model system, and adapted the published SFEB protocols that have been shown to efficiently induce ESCs into GABA receptor alpha 6 + granule cells and L7 + Purkinje neurons via Math1 and Ncam expressing precursors 2427 (Fig. 8a).…”
Section: Resultsmentioning
confidence: 99%
“…The Math1 or Zic1 positive precursors could be further induced into GABA receptor alpha 6 positive granule cells and L7 positive Purkinje neurons on day 20 of ESC in vitro differentiation 24, 27 . The expression of Purkinje cell marker L7 was detected by immunofluorescence staining of day 20 neuronal cell cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we set out to discover new synthetic substrates that support neuron cell culture looking at both primary mouse neurons and mouse embryonic stem cell–derived neural progenitor cells (NPCs) . Primary neurons are an archetypal source for cell replacement therapy in human neurodegenerative diseases, while the electrical responses of NPCs are well characterized in a range of neurobiological studies, and as such are highly relevant for the evaluation of new biomaterials suitable for functional neuron culture.…”
Section: Characterization Of the “Hit” Polymers With The Details Of Tmentioning
confidence: 99%
“…Several studies have shown that BGCs play a crucial role in regulating the movement of granule cell progenitors from the external germinal zone (EGZ) to the granular layer. BGCs have been suggested to share similar interactions with other neurons such as PCs and promote their migration (Higuera et al, 2017). Therefore, the PCs-BGCs intercellular crosstalk at P2-P7, is a likely prerequisite for a coupled migration and for the ability to form a definitive PC layer (Rahimi-Balaei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%